Short-term Beneficial Effects of 12 Sessions of Neurofeedback on Avoidant Personality Accentuation in the Treatment of Alcohol Use Disorder - Dalkner, Nina; Unterrainer, Human F.; Wood, Guilherme; Skliris, Dimitris; Holasek, Sandra J.; Gruzelier, John H.; Neuper, Christa (Frontiers in Psychology, 2017)
This study evaluated the effects of alpha/theta neurofeedback on Clinical Personality Accentuations in individuals with alcohol use disorder. Twenty-five males were investigated using a pre-test/post-test design with a waiting-list control group. Participants were randomly assigned either to an experimental group (n=13) receiving twelve sessions of neurofeedback twice a week as a treatment adjunct over a period of six weeks, or to a control group (n=12) receiving treatment as usual. The Inventory of Clinical Personality Accentuations and the NEO-Five-Factor Inventory were applied at pre- and post-test. The neurofeedback protocol focused on enhancement of the EEG alpha (8-12 Hz) and theta (4-7 Hz) and used a visual feedback paradigm. Analyses of covariance showed improvements in Avoidant Personality Accentuation within the experimental group. Our data suggest that twelve sessions of this neurofeedback intervention might be effective in reducing avoidant and stress-related personality traits in patients with alcohol use disorder.